Navigating Local Governance Dynamics: Strategies for Effective Research and Innovation Implementation in Pandeglang Banten - Nugroho, Arif; Jumanah, Jumanah (PINISI Discretion Review, 2024)
This research is motivated by the opportunity to address issues in the Pandeglang Regency through government policy innovation. Innovation can be an effective strategy to drive growth, productivity, and economic progress at the local and national levels. The research aims to analyze the establishment of the Regional Research and Innovation Agency (BRIDA) to assist the government in making scientifically informed policies. Methodology a qualitative approach was employed, utilizing interviews and documentary studies analyzed through Miles & Huberman's procedures (2009). Findings the research results indicate that BRIDA has the potential to contribute to the acceleration of development, enhancement of regional competitiveness, improvement of governance, and the well-being of the community. It also underscores the urgency of comprehensive research in analyzing complex issues. Originality the recommendation from the research is the integration with other regional agencies to form the Regional Planning and Development, Research, and Innovation Agency (BAPPERIDA) to aid in the administration of regional governance, particularly in the areas of research, development (research and innovation), assessment, implementation, as well as integrated invention and innovation in the region.